1985
DOI: 10.1111/j.1476-5381.1985.tb16150.x
|View full text |Cite
|
Sign up to set email alerts
|

Sodium load and high affinity ouabain binding in rat and guinea‐pig cardiac tissue

Abstract: An estimation of the actual Na/K‐ATPase transport activity in intact cardiac cells was made by measuring the binding of [3H]‐ouabain to rat and guinea‐pig ventricular strips. At the low [3H]‐ouabain concentration of 1 nm equilibrium binding was hardly obtained after an incubation time of five hours. Different procedures known to alter the sodium load of the cardiac preparations influenced [3H]‐ouabain binding: the sodium ionophore monensin enhanced [3H]‐ouabain binding, the local anaesthetic dibucaine and a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Since dihydroouabain exhibited a higher potency in increasing aka and force of contraction in atrial than in ventricular myocardium, a high affinity isozyme of Na+,K+-ATPase could have prevailed in this type of tissue. On the other hand, the higher level of aka in atrial cells could have enhanced the turnover rate of the Na+ pump and thus increased the apparent affinity of Na'.K+-ATPase for the cardioactive steroid (Herzig & Mohr, 1985;Stimers, Lobaugh, Liu, Shigeto & Lieberman, 1990). Our measurement of Na+, K+-ATPase activity in preparations from guinea-pig ventricles and atria showed that the inhibitory potency of dihydroouabain on Na+,K+-ATPase was identical in both tissues (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Since dihydroouabain exhibited a higher potency in increasing aka and force of contraction in atrial than in ventricular myocardium, a high affinity isozyme of Na+,K+-ATPase could have prevailed in this type of tissue. On the other hand, the higher level of aka in atrial cells could have enhanced the turnover rate of the Na+ pump and thus increased the apparent affinity of Na'.K+-ATPase for the cardioactive steroid (Herzig & Mohr, 1985;Stimers, Lobaugh, Liu, Shigeto & Lieberman, 1990). Our measurement of Na+, K+-ATPase activity in preparations from guinea-pig ventricles and atria showed that the inhibitory potency of dihydroouabain on Na+,K+-ATPase was identical in both tissues (Fig.…”
Section: Discussionmentioning
confidence: 68%
“…Inhibition of the ENaC activates the endothelial nitric oxide synthase (eNOS) via phosphorylation and increases the production of NO [31]. In cardiac muscle, an increased sodium load has been shown to activate the Na + /K + -ATPase [17]. In this context, the level of endogenous ouabain, which blocks the Na + /K + -ATPase is increased in patients with hypertension [6,33].…”
Section: Introductionmentioning
confidence: 99%
“…A possible reason for this difference is the higher intracellular Na + concentration present during whole-cell recording. A high c i Na is known to increase the affinity of the Na + /K + pump to cardiac steroids (Herzig and Mohr 1985;Stimers et al 1990;Bielen et al 1992).…”
Section: The Estimated K′ D Valuesmentioning
confidence: 99%